Obesity Paradox, Obesity Orthodox, and the Metabolic Syndrome: An Approach to Unity - Jesse Roth; Navneet Sahota; Priya Patel; Syed F Mehdi; Mohammad M Wiese; Hafiz B Mahboob; Michelle Bravo; Daniel J Eden; Muhammad A Bashir; Amrat Kumar; Farah Alsaati; Irwin J Kurland; et al. (Molecular Medicine, 2016)
Abstract Obesity and its accompanying metabolic syndrome are strongly associated with heightened morbidity and mortality in older adults. In our review of more than 20 epidemiologic studies of major infectious diseases, including tuberculosis, community-acquired pneumonia and sepsis, obesity was associated with better outcomes. A cause-and-effect relationship between over-nutrition and survival with infection is suggested by the results of two preliminary studies of infections in mice, where high-fat feeding for 8–10 wks provided much better outcomes. These better outcomes are reminiscent of many recent studies of “sterile” noninfectious medical and surgical conditions where outcomes for obese patients were better than for their thinner counterparts; this was given the tag “obesity paradox.” Turning to the history of medicine and biological evolution, we hypothesize that metabolic syndrome has ancient origins and is part of a lifelong metabolic program. While that part of the program promotes morbidity and mortality with aging, it helps infants and children as well as adults fight infections and recover from injuries, key events in the centuries before the public health advances of the 20th century. We conclude with speculation on how an understanding of the biological elements that protect obese patients with infections or injuries might be applied advantageously to thin patients with the same medical challenges.